The Cosmopolitanism of Y.B. Mangunwijaya - Rizky Alif Alvian (Institute of International Studies, 2015)
This paper aims to explain and analyze the idea of post-nationalism/post-Indonesia (pasca-nasionalisme/pasca-Indonesia) provided by Indonesian architect, clergy, social activist, and writer, Y.B. Mangunwijaya. Through his idea of post-nationalism, Mangunwijaya criticizes the Indonesian nationalism which tends to ask for an unconditional loyalty of the people to the state. This “shallow nationalism”, according to Mangunwijaya, is well expressed in the slogan of “right or wrong my country” (Mangunwijaya, 1999). Mangunwijaya further argues that the state should only be defended as long as the state defends “truth” since the purpose of human life is not to protect the state; but to defend truth and humanity. However, it is a mistake to understand Mangunwijaya simply as an anti-nationalist thinker. Instead, his idea of post-nationalism is rooted in his experience of third world nationalism, especially Indonesian nationalism. According to him, Indonesian nationalism did not emerge to resist the Dutch. It emerged to resist colonialism and its inhuman nature; and then attempted to restore human dignity. In other words, humanization is the essence of Indonesian nationalism (Mangunwijaya, 1995; 1999). This paper argues that Mangunwijaya reinterpretation of nationalism lays the foundation of his post-nationalism: post-nationalism is an effort to expand the essence of Indonesian nationalism to the world. Mangunwijaya directs Indonesian nationalism not only to humanize his polis, i.e. Indonesia, but also to humanize the cosmos, the world. This cosmopolitan aspect of Mangunwijaya post-nationalism is unique compared to that of Kantian or Levinasian-Derridean cosmopolitanism. Instead of placing nationalism as an obstacle to build a cosmopolitan world, Mangunwijaya places nationalism in the heart of his cosmopolitanism.